Treatment of duodenal peptic ulcer perforation by endoscopic clips: A novel approach - Joshi, Mohan Achyut; Gadhire, Minakshi; Paranjpe, Ashwini Arun (Journal of Digestive Endoscopy, 2017)
Aims and Objectives: In an attempt to avoid the high morbidity and mortality associated with exploratory laparotomy in a patient of duodenal ulcer perforation (DUP), an attempt was made to treat patients with spontaneous DUP with endoscopic clips. Background: DUP is a common cause of surgical emergency. Traditional form of treatment includes nasogastric decompression, fluid resuscitation, and exploratory laparotomy or laparoscopy for repair. Considering the compromised state of such patients, endoscopic treatment and avoiding surgery will play a great role in preventing the further stress caused by surgery and facilitate quicker recovery. On thorough review of literature, we found few articles stating successful endoscopic clipping of iatrogenic duodenal perforation occurred during upper endoscopy. Our case series appears to be first of its kind reporting the use of endoclips for treating spontaneous (noniatrogenic) DUP. Materials and Methods: Three young male patients presenting with a short duration history of abdominal pain and vomiting and chest radiograph suggesting pneumoperitoneum were selected for endoscopic clipping. All of them were hemodynamically stable with near normal blood pressure and pulse rate. Under local anesthetic spray and mild sedation, endoscopic clipping was carried out along with supportive treatment. Postoperatively, patients were monitored clinically and radiographically and discharged after they could tolerate full diet. Results and Conclusion: We recommend that in selected group of young patients of DUP who have presented early and are hemodynamically stable, endoclips may be applied to approximate mucosa. With supportive conservative treatment offered, thereafter healing of perforation occurs without the need for laparotomy or laparoscopy for suturing the same.
Keywords: Duodenal ulcer perforation; endoclip; upper endoscopy